Substantial decline in energy storage and stomach fullness in Antarctic minke whales (Balaenoptera bonaerensis) during the 1990s - Konishi, Kenji; Wolloe, Lars (J. Cetacean Res. Manage., 2023)
A substantial decline in energy storage in the Antarctic minke whale during the 18-year Japanese JARPA research programme (austral summers 1987/88–2004/05) was reported in 2008 (Konishi et al., 2008). The statistical method used in the study was simple multiple linear regression. The results have since been thoroughly discussed by the Scientific Committee of the International Whaling Commission because of the potential importance of the findings. Some had suggested that the sampling heterogeneity in the JARPA data was so substantial that generalised linear models (GLMs) with interaction terms and random-effects terms should be explored. For the present article, five response variables related to energy storage and the variable ‘stomach content weight’ are systematically analysed using GLMs. For all five energy storage variables, the results show declines in the interval 3% to 9% over the JARPA period, all significantly different from zero at the 5% level, but no later decline. The weight of sieved stomach contents declined by 25% over the same period. The coefficients of the decline and the coefficients for most other independent variables were similar to values obtained by simple linear regression, but in some cases the standard errors were larger. The results indicate that important changes took place in the Antarctic ecosystem during the 1990s. It is hypothesised that the most important cause of the changes was the simultaneous increase in numbers of other krill feeders, especially humpback whales.